The Indonesian Constitutional Court Approaches the Proportionality Principle to the Cases Involving Competing Rights - Lailam, Tanto; Anggia, Putri (PROGRAM STUDI MAGISTER ILMU HUKUM FAKULTAS HUKUM UNIVERSITAS DIPONEGORO SEMARANG, 2023)
The research focuses on the proportionality analysis of the competing socio-economic rights in the Indonesian Constitutional Court / Mahkamah Konstitusi Republik Indonesia (the MKRI). It is motivated by the unclear concept/model of proportionality analysis in Indonesia and its application by the court. The research method used was normative legal research with statutory and case approaches. The MKRI's general practices need to be more structured, unsystematized, and uncomprehensive to implement with four stages: legitimate aims, suitability, necessity, and balancing. It applies a model that refers to the legal objectives based on Pancasila and the 1945 Constitution. It declares the balance of fundamental rights and obligations of citizens based on the values of the godhead, humanity, unity, democracy, and social justice. Hence, some decisions used proportionality analysis, specifically in economic rights. Its implications create a balance of legal norms and integratively value legal certainty, justice, and legal expediency.